Delivering on the Promise of Entrepreneurship by Thinking Beyond Limiting Economics Assumptions: An Extension of Lewis et al.’s “A Promise Not (Yet) Fulfilled” - Villesèche, Florence; Ramoglou, Stratos; Costanzo, Laura (Academy of Management Review, 2026)
Since Shane and Venkataraman's (2000) seminal paper, entrepreneurship research has been preoccupied with the exploitation of entrepreneurial opportunities.Lewis, Bruton and Shepherd (2024) (LBS hereafter) fruitfully shift focus from "which opportunities are exploited to which opportunities are not" (p.11).Trying to answer why-not questions is critical to advancing theoretical understanding of how nonactual but desirable futures can be realized.As importantly, understanding why the needs of marginalized consumers are not served is imperative for building more inclusive capitalist societies.LBS address this lacuna by providing several conceptual innovations.They explain that market inefficiencies are grounded in structural disadvantage resulting from social closure, segregation, and stereotyping of marginalized consumers.This insight is not only radical for